Bioflok Technology In Local Shrimp Cultivation Systems In Efforts To Improve The Economy And As An Education Village In Pante Ceureeumen District, West Aceh - Farah Diana; Mahendra Mahendra (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2022)
This research-based service program aims to seek to develop the research results of the proposing team for community empowerment. The application of the research results was carried out on the biofloc technology program in local shrimp farming systems in an effort to increase the economy and as an educational village in Pante Ceureumen District, West Aceh which is a potential aquaculture that must be developed. The application system is local shrimp farming with biofloc technology. Biofloc technology is a cultivation technique through environmental engineering that relies on oxygen supply and the use of microorganisms that can directly increase the digestibility value of feed. This service activity aims to increase farmers' income with high shrimp productivity and increase local shrimp production. The activity was carried out for 6 months in Pante Ceureumen District, West Aceh. The results obtained are to reduce production costs by 54% until the harvest is 90 days. The outputs that will be produced are in the form of international journals, services, and methods as well as mass media.